Diversidad de artrópodos en las fitotelmata de la planta huésped Calathea capitata (Zingiberales; Marantaceae) de Perú - Dendi, Divya (2023)
Cryptic habitats are often overlooked in biodiversity surveys. Phytotelmata, or plant pools, are one type of cryptic habitat that supports diverse fauna in a miniature ecosystem. This study surveys the arthropod community of two types of phytotelmata, bracts and leaf rolls, on a single species, Calathea capitata (Ruiz and Pav.) Lindl. (Zingiberales: Marantaceae), from one Amazon site in Peru. Specimens were collected from eight bracts and eight leaf rolls. A total of 55 arthropods (36 adults, 19 juveniles) were found in both phytotelmata types. In the bract samples were found: spiders (Araneae: Corinnidae), beetles (Coleoptera: Carabidae, Erotylidae, Staphylindae), flies (Diptera: Limoniidae), a leafhopper nymph (Hemiptera: Cicadellidae), ants (Hymenoptera: Formicidae), and unidentified larvae. In leaf roll samples were found: Leaf beetles (Coleoptera: Chrysomelidae), an earwig (Dermaptera: Spongiforidae), flies (Diptera: Drosophilidae), and an adult leafhopper (Hemiptera: Cicadellidae). A similar survey of Calathea lutea Schultes in Peru revealed a community dominated by Coleoptera in leaf rolls and Diptera in bracts, with a few Dermaptera and Hymenoptera, but no Araneae or Hemiptera. This study demonstrates that phytotelmata host diverse taxa and serve as a nursery to immature stages thus impacting the life cycles of local fauna, which in turn affect local biodiversity.